2011
DOI: 10.1021/nn203520v
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Rectification in Donor–Acceptor Molecular Heterojunctions

Abstract: The transport properties of a junction consisting of small donor-acceptor molecules bound to Au electrodes are studied and understood in terms of its hybrid donor-acceptor-electrode interfaces. A newly synthesized donor-acceptor molecule consisting of a bithiophene donor and a naphthalenediimide acceptor separated by a conjugated phenylacetylene bridge and a nonconjugated end group shows rectification in the reverse polarization, behavior opposite to that observed in mesoscopic p-n junctions. Solution-based sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 29 publications
(46 reference statements)
0
70
1
Order By: Relevance
“…Indeed, most molecular diodes based on, for instance, asymmetric molecule−electrode contacts, 14−16 embedded dipoles (or push−pull molecules), 17 donor−bridge−acceptor moieties (following the original design by Ratner and Aviram 18 ), or one asymmetrically positioned donor or acceptor group inside the junction, 19−21 yielded so far rectification ratios R = |J(V for )/J(V rev )| < 10 (V for = forward bias; V rev = reverse bias; J = current density in A/cm 2 ). 22 −25 Stadler et al 23 showed theoretically that molecular diodes in the coherent tunneling regime likely cannot achieve values of R > 20.…”
Section: Olecular Electronics Is Complementary To Conventionalmentioning
confidence: 99%
“…Indeed, most molecular diodes based on, for instance, asymmetric molecule−electrode contacts, 14−16 embedded dipoles (or push−pull molecules), 17 donor−bridge−acceptor moieties (following the original design by Ratner and Aviram 18 ), or one asymmetrically positioned donor or acceptor group inside the junction, 19−21 yielded so far rectification ratios R = |J(V for )/J(V rev )| < 10 (V for = forward bias; V rev = reverse bias; J = current density in A/cm 2 ). 22 −25 Stadler et al 23 showed theoretically that molecular diodes in the coherent tunneling regime likely cannot achieve values of R > 20.…”
Section: Olecular Electronics Is Complementary To Conventionalmentioning
confidence: 99%
“…The experimental attempts of a single-molecule rectifier will pave steps towards future functional molecular electronic devices. Since first proposed by Aviram and Ratner, 1 molecular rectifier has gained considerable attention in both experimental designs [2][3][4][5] and theoretical simulations. 6,7 One of the most promising candidates stems from a molecular heterojunction which describes a molecular junction with asymmetric conformation.…”
Section: Introductionmentioning
confidence: 99%
“…The geometric optimization as well as calculations of the electronic structure and transport are performed by using the spin-polarized DFT combined with the non-equilibrium Green's function (NEGF) method [12], which has been confirmed that they are able to give results agreeing quantitatively well with experiments [13][14][15]. We employ Troullier-Martins norm-conserving pseudopotentials to represent the atom core and linear combinations of local atomic orbitals to expand the valence states of electrons.…”
Section: Structure Model and Theoretical Methodsmentioning
confidence: 91%